ANALISIS MARKET PERFORMANCE DENGAN PENDEKATAN CAPM DAN APPRAISAL RATIO SERTA PENGARUHNYA TERHADAP VARIASI HARGA SAHAM SYARIAH - Aisyah, Esy Nur (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2015)
Abstract The success of Jakarta Islamic Index as an index that has the largest market capitalization that is visible from the aggregate value of shares JII significantly compared to the capitalization of all shares diperdagangkan.Namun active in a market, there are always investors who do not agree with the market consensus due to stock market performance is not always walk in the same direction with high market capitalization. For companies that go public stock prices is an indicator of the value perusahaan.Oleh Therefore, this study aimed to examine the determinants of stock prices in the Indonesian sharia (JII) over a period of four years from 2011 to 2014. The regression analysis of six independent variables associated with the use of data from shares of sharia (JII) listed on the Stock Exchange. Based on the analysis of CAPM, there are 5 stocks undervalued, and 8 shares were overvalued. Then based on the analysis appraisal ratio, the stock with the top three rankings are; SMGR, ASRI, and CPIN. Adjusted R-square value (0.833) indicates that the stock prices of sharia nearly 83% depending on the independent variables are EVA, EPS, DPS, ROE, PER, DER, Indonesian Interest Rate, Composite Index, and Inflation. Significance test showed that EPS and PER is an important determinant of stock prices sharia in Indonesia. On the other hand, the research also found that variables EVA, DER, DPS, ROE, Indonesian Interest Rate, and Inflation is not powerful explanatory variables to determine the price of shares of sharia in Indonesia